Book Review - 1917: La Revolución Rusa Cien Años Después - Alejandro Perna (Slovo, 2022)
Jorge Saborido's 1917. La Revolución Rusa cien años después provides a useful introduction to a complex topic. Mainly a work of synthesis, the author manages to cover several thematic areas while bringing to the attention of the reader different interpretations to some of the most contentious events. In spite of minor drawbacks, it provides a solid overview of the subject from which Spanish-speaking undergraduates and non-specialists may profit.
Keywords: Russian Revolution; Russian History